Question
upstudy study bank question image url

\begin{tabular}{l} EXERCISE 9 \\ Simplify the expressions as far as possible. \\ \( \begin{array}{l}1 \quad \frac{\tan \left(180^{\circ}-x\right) \cdot \sin \left(360^{\circ}-x\right) \cdot \cos \left(90^{\circ}-x\right)}{\sin \left(180^{\circ}+x\right) \cdot \cos \left(90^{\circ}+x\right) \cdot \tan \left(180^{\circ}+x\right)} \\ 2 \quad \frac{\sin \left(180^{\circ}+\theta\right) \cdot \cos \left(360^{\circ}-\theta\right) \cdot \tan (-\theta)}{2 \cos \left(90^{\circ}+\theta\right) \cdot \sin \left(90^{\circ}+\theta\right)} \\ \frac{2 \sin \left(90^{\circ}-x\right)+\cos \left(180^{\circ}-x\right)}{\sin \left(90^{\circ}-x\right)-\cos \left(x-180^{\circ}\right)} \\ \cos \left(90^{\circ}-\beta\right)+\cos \left(\beta+90^{\circ}\right)+\cos \left(180^{\circ}-\beta\right)-\cos \left(\beta+180^{\circ}\right)+\cos (-\beta) \\ {\left[\cos \left(90^{\circ}+x\right) \cos (-x) \tan \left(360^{\circ}-x\right)\right]-\left[\cos \left(360^{\circ}-x\right) \sin \left(x-90^{\circ}\right)\right]} \\ {\left[\sin \left(180^{\circ}-x\right)+\sin \left(90^{\circ}-x\right)\right]\left[\cos \left(90^{\circ}-x\right)+\cos (-x)\right]} \\ \\ \frac{\tan \left(180^{\circ}+x\right) \cdot \sin \left(90^{\circ}-x\right)}{\cos \left(90^{\circ}-x\right)}-\frac{\cos \left(180^{\circ}-x\right)}{\sin \left(90^{\circ}+x\right)} \\ \cos \left(90^{\circ}-\theta\right) \cdot \tan \left(180^{\circ}+\theta\right) \cdot \cos \left(360^{\circ}-\theta\right)-\cos (-\theta) \cdot \sin \left(\theta-90^{\circ}\right)\end{array} \) \\ \hline\end{tabular}

Ask by Chavez Rojas. in South Africa
Mar 08,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

1. The expression simplifies to 1. 2. The expression simplifies to \(-\frac{1}{2}\tan\theta\). 3. The expression simplifies to \(\frac{1}{2}\). 4. The expression simplifies to \(\cos\beta\). 5. The expression simplifies to 1. 6. The expression simplifies to \(\left[\sin(180^\circ - x) + \sin(90^\circ - x)\right]\left[\cos(90^\circ - x) + \cos(-x)\right]\).

Solution

1) We have \[ \frac{\tan(180^\circ-x)\cdot\sin(360^\circ-x)\cdot\cos(90^\circ-x)} {\sin(180^\circ+x)\cdot\cos(90^\circ+x)\cdot\tan(180^\circ+x)}. \] Recall: \[ \begin{aligned} \tan(180^\circ-x) &= -\tan x,\\[1mm] \tan(180^\circ+x) &= \tan x,\\[1mm] \sin(360^\circ-x) &= -\sin x,\\[1mm] \sin(180^\circ+x) &= -\sin x,\\[1mm] \cos(90^\circ-x) &= \sin x,\\[1mm] \cos(90^\circ+x) &= -\sin x. \end{aligned} \] Substitute into the expression: \[ \begin{aligned} \text{Numerator} &= (-\tan x)\cdot (-\sin x)\cdot (\sin x) = \tan x\cdot\sin^2 x,\\[1mm] \text{Denominator} &= (-\sin x)\cdot (-\sin x)\cdot (\tan x) = \sin^2 x\cdot\tan x. \end{aligned} \] Thus, \[ \frac{\tan x\cdot\sin^2 x}{\sin^2 x\cdot\tan x}= 1. \] 2) The expression is \[ \frac{\sin(180^\circ+\theta)\cdot\cos(360^\circ-\theta)\cdot\tan(-\theta)} {2\cos(90^\circ+\theta)\cdot\sin(90^\circ+\theta)}. \] Using: \[ \begin{aligned} \sin(180^\circ+\theta) &= -\sin\theta,\\[1mm] \cos(360^\circ-\theta) &= \cos\theta,\\[1mm] \tan(-\theta) &= -\tan\theta,\\[1mm] \cos(90^\circ+\theta) &= -\sin\theta,\\[1mm] \sin(90^\circ+\theta) &= \cos\theta, \end{aligned} \] the numerator becomes: \[ (-\sin\theta)\cdot\cos\theta\cdot(-\tan\theta) =\sin\theta\cos\theta\tan\theta. \] The denominator is: \[ 2\cdot(-\sin\theta)\cdot\cos\theta=-2\sin\theta\cos\theta. \] Since \(\tan\theta=\frac{\sin\theta}{\cos\theta}\), the numerator simplifies to: \[ \sin\theta\cos\theta\cdot\frac{\sin\theta}{\cos\theta}=\sin^2\theta. \] Therefore, the entire expression is: \[ \frac{\sin^2\theta}{-2\sin\theta\cos\theta} =\frac{\sin\theta}{-2\cos\theta} =-\frac{1}{2}\tan\theta. \] 3) We need to simplify \[ \frac{2\sin(90^\circ-x)+\cos(180^\circ-x)} {\sin(90^\circ-x)-\cos(x-180^\circ)}. \] Recall: \[ \begin{aligned} \sin(90^\circ-x)&=\cos x,\\[1mm] \cos(180^\circ-x)&=-\cos x,\\[1mm] \cos(x-180^\circ)&=\cos(180^\circ-x)=-\cos x. \end{aligned} \] Thus the numerator is: \[ 2\cos x+(-\cos x)=\cos x, \] and the denominator is: \[ \cos x-(-\cos x)= 2\cos x. \] So the expression becomes: \[ \frac{\cos x}{2\cos x}=\frac{1}{2}. \] 4) The expression \[ \cos(90^\circ-\beta)+\cos(\beta+90^\circ)+\cos(180^\circ-\beta)-\cos(\beta+180^\circ)+\cos(-\beta) \] simplifies using: \[ \begin{aligned} \cos(90^\circ-\beta)&=\sin\beta,\\[1mm] \cos(\beta+90^\circ)&=-\sin\beta,\\[1mm] \cos(180^\circ-\beta)&=-\cos\beta,\\[1mm] \cos(\beta+180^\circ)&=-\cos\beta,\\[1mm] \cos(-\beta)&=\cos\beta. \end{aligned} \] Then, \[ \sin\beta+(-\sin\beta)=0, \] and \[ \cos(180^\circ-\beta)-\cos(\beta+180^\circ)=(-\cos\beta)-(-\cos\beta)=0. \] Adding the last term, we obtain: \[ 0+ \cos\beta = \cos\beta. \] 5) We have \[ \left[\cos(90^\circ+x)\cos(-x)\tan(360^\circ-x)\right]-\left[\cos(360^\circ-x) \sin(x-90^\circ)\right]. \] Apply: \[ \begin{aligned} \cos(90^\circ+x)&=-\sin x,\\[1mm] \cos(-x)&=\cos x,\\[1mm] \tan(360^\circ-x)&=\tan(-x)=-\tan x,\\[1mm] \cos(360^\circ-x)&=\cos x,\\[1mm] \sin(x-90^\circ)&=-\cos x. \end{aligned} \] Then the first bracket is: \[ (-\sin x)(\cos x)(-\tan x)=\sin x\cos x\,\tan x. \] Since \(\tan x=\frac{\sin x}{\cos x}\), it becomes: \[ \sin x\cos x\,\frac{\sin x}{\cos x}=\sin^2x. \] The second bracket is: \[ \cos x\cdot(-\cos x)=-\cos^2x. \] Thus the whole expression is: \[ \sin^2x -(-\cos^2x) =\sin^2x+\cos^2x=1. \] 6) The expression is \[ \left[\sin(180^\circ-x)+\sin(90^\circ-x)\right] \left[\cos(90^\circ-x)+\cos(-x)\right]. \] Recall: \[ \begin{aligned} \sin(180^\circ

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

Let’s break down each part of your exercise and simplify the expressions step-by-step with some fun thrown in! 1. In your expression, recall that \(\tan(180^{\circ}-x) = -\tan(x)\) and \(\sin(360^{\circ}-x) = -\sin(x)\). Using these relationships, we can manipulate the expression into a simpler form. Additionally, notice that \(\cos(90^{\circ}-x) = \sin(x)\) and \(\sin(180^{\circ}+x) = -\sin(x)\). With this knowledge, you can reduce the entire fraction drastically! 2. Here’s a fun fact: \(\tan(-\theta) = -\tan(\theta)\) and \(\cos(360^{\circ}-\theta) = \cos(\theta)\). Applying these trigonometric identities can make the simplification process a joy! When simplifying the denominator, remember that \(\cos(90^{\circ}+\theta) = -\sin(\theta)\) and \(\sin(90^{\circ}+\theta) = \cos(\theta)\). This brings everything together in a straightforward way, so keep your trigonometric identities handy for the next steps! Happy simplifying!

Related Questions

Latest Trigonometry Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy